ANALISIS KEAMANAN JARINGAN PADA FASILITAS INTERNET TERHADAP SERANGAN SYSTEM FAILURE PADA TOKO SERVICES W-ELEKTRIK BATAM - Nofedrinata, Windri; Maslan, Andi (Computer Science and Industrial Engineering, 2023)
The research entitled Analysis of Network Security in Internet Facilities (Wifi) Against System Failure Attacks at the Batam W-Electric Service Shop is expected to help analyze network protocols and review network security. The technique used in this study is a descriptive approach, where this strategy is used to parse information by describing the information that has been collected without making changes when conducting research at the Batam W-Electric Service Store. Based on directed research, this shows how research in the W-Electric Service Store can be intercepted using ettercap and can be easily attacked in the form of a trojan, which is a wiretapping cycle by sending packets. Therefore it is suggested to the W-Elektrik Service Shop to further develop network security so that it is not easily hacked and attacked like a trojan.